Reaktualisasi Konsep Raḍā - Nurpah, Nurpah (IAIN Palangka Raya, 2016)
Lack of good nutrition for pregnant and lactating mothers cause reduced productivity smoothly for all mothers breastfeeding postpartum. Various problems that arise then in this study focuses on the obligations How can the mother in delivering the first food intake according to QS. Al-Baqarah [2]: 233. The type this study is a library research, where the data analysis method is double movement that popularized by Fazlur Rahman. Results